Pengaruh Kompetensi, Budaya Organisasi dan Komitmen terhadap Kinerja Karyawan Pada PT. PLN ( Persero ) UIP3B Sumatera UPT Palembang - Syahyuni; Syaiful Sahri; Dita Marisa Putri (Fakultas Ekonomi Universitas Tridinanti Palembang, 2024)
Abstract : This study discusses the Effect of Competence (X.1), Organizational Culture (X2) and Commitment (X3) on employee performance (Y) which aims to examine the effect of Competence, Organizational Culture and Commitment on employee performance at PT. PLN (Persero) UIP3B Sumatra UPT Palembang. The samples used in this study were 55 employees with the saturated sample method. The data used are primary data and secondary data. Data collection using a questionnaire and hypothesis testing using multiple regression analysis using the help of the SPSS 24.0 program. The results of this test state that Competency, Organizational Culture, and Commitment have a positive and significant effect on employee performance. From the research conducted, the authors conclude that Competency, Organizational Culture, and Commitment have positive direction coefficients on employee performance, Competency Correlation Coefficient, Organizational Culture, Commitment with Positive Correlation. Based on the Competency t test (X1) significantly influence employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where is tilapia X1 of 3,780 with a significant 0,000 <0.05, while Based on the t test Organizational Culture (X2) significantly influence employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where the tcount X1 of 5,228 with a significant 0,000 <0.05, and Based on the t test Commitment (X3) has a significant effect on employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where is tilapia X1 of 3,780 with a significant 0.015 <0.05. Abstrak : Tujuan penelitian ini adalah mengeksplorasi peran modal intelektual terhadap kinerja perusahaan yang mengarah pada peningkatan daya saing yang berkelanjutan. Dengan mengintegrasi modal intelektual (human capital, relational capital, dan spiritual capital) dan kinerja, kemudian menghubungkan dengan peningkatan daya saing. Secara khusus, hal ini berkaitan dengan bagaimana menghasilkan model hubungan antara modal intelektual yang dapat digunakan untuk mengembangkan kinerja perusahaan yang baik sehingga dapat meningkatkan daya saing. Sampel adalah karyawan sejumlah 100 orang, data dikumpulkan melalui penyebaran kuesioner dalam satu waktu (cross section) dengan Teknik analisis yaitu SEM-PLS menggunakan SMARTPLS. Hasil penelitian mengungkap bahwa modal manusia dan spiritual berpengaruh signifikan terhadap modal intelektual, daya saing memediasi hubungan antara modal intelektual dengan kinerja perusahaan.